Situating the Rural Teacher Labor Market in the Broader Context: A Descriptive Analysis of the Market Dynamics in New York State - Luke C. Miller (Journal of Research in Rural Education, 2012)
Expanding accountability systems that impose policies across all schools have amplifi ed assertions that rural teacher labor markets differ from non-rural labor markets in meaningful ways that complicate rural schools' efforts to comply with the policy directives. The analysis presented here examines this claim by exploring teacher labor market trends over a 20-year period across community type in the New York state. Rural schools rely on beginning teachers to meet their demand more so than schools in non-rural communities. The percentage of teachers with no previous experience is higher in rural than non-rural communities, and experienced teachers transfer from rural to non-rural schools. Same-school retention rates are lower in rural schools than in suburban schools and experienced teachers transfer away on net from rural schools to suburban schools. Salaries may be a contributing factor to these labor market trends. Rural salaries, both beginning and average, have consistently been the lowest in the state yet are among the highest once adjusted for regional costs differences. The analysis presented here provides valuable contextual information for future analyses as well as for policymakers wishing to provide fl exibility to rural schools to comply with universal policies.